2020
DOI: 10.1177/2045894019873548
|View full text |Cite
|
Sign up to set email alerts
|

Bisoprolol therapy does not reduce right ventricular sympathetic activity in pulmonary arterial hypertension patients

Abstract: Right ventricular (RV) function and autonomic dysfunction are important determinants of morbidity and mortality in patients with pulmonary arterial hypertension (PAH). Although successful in animal studies, effects of beta-blocker therapy on RV function in clinical trials were disappointing. To understand this discrepancy, we studied whether beta-blocker therapy changes RV sympathetic activity. Idiopathic PAH (IPAH) patients received beta-blocker therapy (uptitrated to a maximal tolerated dose) and underwent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…62 Recommendations for Future Research • Define the normal molecular (genomic, metabolomic, and proteomic) and cellular RV profile as well as the effect of perturbations of these factors. 49,[63][64][65][66] The development of an effective therapy for RV remodeling and dysfunction will face distinct challenges, including (1) inability to use short-term exercise capacity as a primary end point in trials of beta-blockers and possibly other drug classes 67 ; (2) lack of end points focused on remodeling in left-sided heart disease (including improved ventricular function) that are accepted by the Food and Drug Administration and other regulatory agencies; (3) potential proarrhythmic properties of therapies that either (a) initially depress ventricular function before improving it or (b) are inotropes; and (4) the requirement that investigators have equipoise.…”
Section: Understanding the Pathobiology Of The Rvmentioning
confidence: 99%
“…62 Recommendations for Future Research • Define the normal molecular (genomic, metabolomic, and proteomic) and cellular RV profile as well as the effect of perturbations of these factors. 49,[63][64][65][66] The development of an effective therapy for RV remodeling and dysfunction will face distinct challenges, including (1) inability to use short-term exercise capacity as a primary end point in trials of beta-blockers and possibly other drug classes 67 ; (2) lack of end points focused on remodeling in left-sided heart disease (including improved ventricular function) that are accepted by the Food and Drug Administration and other regulatory agencies; (3) potential proarrhythmic properties of therapies that either (a) initially depress ventricular function before improving it or (b) are inotropes; and (4) the requirement that investigators have equipoise.…”
Section: Understanding the Pathobiology Of The Rvmentioning
confidence: 99%
“…Important triggers for SNS activation are atrial and ventricular stretch: β-AR expression is downregulated specifically in the right ventricle but not in the left ventricle in PAH patients [43], and was related to ventricular wall stress [44]. The role of atrial stretch on SNS activation was shown in studies investigating balloon atrial septostomy.…”
Section: Local Changes In the Autonomic Nervous Systemmentioning
confidence: 99%
“…Currently, β-blocker application is not recommended for PAH due to their negative inotropic and chronotropic effects. Clinical studies on the use of β-blockers in PAH had inconsistent results dependent on whether the β1-selective bisoprolol (20,21), or β1-and α1-blockade (carvedilol) was employed. Carvedilol was safe in PAH patients and even normalized pathologically increased RV glucose uptake in PAH (18).…”
Section: Beta-adrenoceptor Antagonistsmentioning
confidence: 99%